The resource role of flowering woody plants in increasing the insects biological diversity - Kuzmina Tatiana (EDP Sciences, 2021)
The aim of the study was to assess the resource role of flowering woody plants in maintaining the biological diversity of insects. The studies were carried out in 2019–2020 in the northern forest-steppe of the Ob region during the flowering period of woody plants from the Oleaceae family of the genus Syringa: S. josikaea J. and S. vulgaris L. Insects were collected by mowing with an entomological net in the crowns and under-crown space. The flowering of plants attracted insects from more than 25 families from 7 orders. The largest number of insects belonged to the order Thysanoptera 79.2%, followed by representatives of the orders Hemiptera (7.1%) and Diptera (6.4%). The entomological faunas of S. josikaea and S. vulgaris differed significantly in their taxonomic composition, insects abundance, and their association with flowering periods. Low coefficients of similarity and high power of the factor “plant species” influence on biological diversity and the insects number were revealed. S. josikaea played a more significant role in maintaining the biological diversity of insects. Research showed that insects are associated with a certain species of woody plant.